2003
DOI: 10.1111/1467-9620.00267
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Forms of School Organization

Abstract: This article argues that new forms of school organization are emerging that do not fit the classical definitions of public and private schools. Three case study schools are used to explore the critical features of the public-private distinction in American schooling. We focus on the fuzzy boundary between schools that are clearly public and those that are clearly private. It is our contention that the shared characteristics between public and private schools are sufficiently stabilized to contain the ground fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Included in these formal relationships are often means for evaluating if the partnership is successful in addressing district goals. Thus, the nature of contracting in Philadelphia is not about turning over control to private entities but about cross-sectoral collaboration and joint ventures with blurred boundaries between public and private (Gold et al, in press;Henig, Holyoke, Lacireno-Paquet, & Moser, 2003;Rufos-Lignos & Richards, 2003;Wohlstetter, Malloy, Smith, & Hentschke, 2004). Overall, the rhetoric of the reform has been about bringing in the private sector to support and enhance reform efforts through "much-needed managerial and technological expertise, new ideas, an entrepreneurial spirit, and material resources" (Useem, 2005, p. 8).…”
Section: Changes In District Management and Public-private Engagementmentioning
confidence: 99%
“…Included in these formal relationships are often means for evaluating if the partnership is successful in addressing district goals. Thus, the nature of contracting in Philadelphia is not about turning over control to private entities but about cross-sectoral collaboration and joint ventures with blurred boundaries between public and private (Gold et al, in press;Henig, Holyoke, Lacireno-Paquet, & Moser, 2003;Rufos-Lignos & Richards, 2003;Wohlstetter, Malloy, Smith, & Hentschke, 2004). Overall, the rhetoric of the reform has been about bringing in the private sector to support and enhance reform efforts through "much-needed managerial and technological expertise, new ideas, an entrepreneurial spirit, and material resources" (Useem, 2005, p. 8).…”
Section: Changes In District Management and Public-private Engagementmentioning
confidence: 99%
“…Levin and Belfield, 2003; Dijkstra et al , 2001; Onderwijsraad, 2005). In a study of public and private schools in the USA, Rufo‐Lignos and Richards (2003) found that the boundary between the public and the private sectors is blurred and that clear differences between public and private schools are lacking. Bottery (2005) describes an invasion of private sector beliefs and practices in education in the Western world.…”
Section: Introductionmentioning
confidence: 99%